Show that


I have proved it for $n=2$ by defining


which means that $$-b=a_2-\frac{a_1+a_2}2$$

then rewriting the equation for $n=2$

$$a_1a_2 \le \left(\frac{a_1+a_2}2\right)^2$$

then substituting $b$ into the right hand side


$$a_1a_2= \left(\frac{a_1+a_2}2\right)^2-b^2$$

and as $b^2$ is always positive then $\displaystyle a_1a_2 \le \left(\frac{a_1+a_2}2\right)^2$must be true

However this is when I run into the problem of how to prove this for $n+1$, any help would be greatly appreciated


Given $a_1,a_2,\ldots,a_{n+1}\geq 0$, let $A:=\frac{a_1+a_2+\ldots+a_{n+1}}{n+1}$. Define $b_i:=\sqrt{a_i\,A}$ for $i=1,2,\ldots,n-1$ and $b_n:=\sqrt{a_{n-1}a_n}$. Apply AM-GM for $n$ variables on the $b_i$'s, and then apply AM-GM on $2$ variables on each $b_i$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.